(untitled) (Research, Society and Development, 2022)
This article aims to specify like is importance of Reverse Logistics, given that the present market context is of extreme competition and an aspect that is only now beginning to have a careful look on part of companies. In This regarding about companies, has found in reverse logistics an efficient way to adopt more sustainable principles, since reverse logistics can be defined as the management of the flow of materials from their point of consumption to the point of origin, which needs to be managed. It was noted that Reverse Logistics can be used in other sectors in economy, but still finds a lot of difficulties and needs to adapt to this business environment. In addition, presenting differentiation in customer service, as the manufacturer has more accessible product return policies, presenting an advantage over the competition. The qualitative research shows positive aspects an implementation in a reverse logistics system, and it has brought an important data, so that it becomes a factor about sustainable development, by researchers in national publications and being part of the strategies in companies from other sectors, because currently all wish to use and producing ecologically correct products.